2007
DOI: 10.1002/qre.878
|View full text |Cite
|
Sign up to set email alerts
|

On the use of principal component analysis to identify systematic patterns in roundness profiles

Abstract: In many industrial applications, quality of products or processes is related to profiles. With reference to mechanical components, profiles and surfaces play a relevant role, as shown by the high number of geometric specifications characterizing most of the technical drawings. In this framework, an important step consists in identifying the systematic pattern which characterizes all the profiles machined while the process is in its standard or nominal state. With reference to this aim, this paper focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 21 publications
3
54
0
Order By: Relevance
“…In the reference case study of this paper, Colosimo and Pacella (2007) showed that the number of PCs to be retained is equal to m = 4. In this last case, the PCA approach can take full advantage of both the T 2 and the Q control charts.…”
Section: Productive Scenarios Under Studymentioning
confidence: 99%
See 4 more Smart Citations
“…In the reference case study of this paper, Colosimo and Pacella (2007) showed that the number of PCs to be retained is equal to m = 4. In this last case, the PCA approach can take full advantage of both the T 2 and the Q control charts.…”
Section: Productive Scenarios Under Studymentioning
confidence: 99%
“…Different approaches can be used to select the proper set of PCs (Jackson 2003). For instance, cross-validation can be effectively used to chose the number m of significant PCs (Colosimo and Pacella 2007). When a subset of m out of the whole number of p PCs is retained (m < p), the original profile can be estimated as:…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations